AROMATIC PLANT OF LAMIACEAE FAMILY FOR USE IN PHYTOTHERAPY - L. A. Logvinenko; L. A. Khlypenko; N. V. Marko (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2016)
Introduction. Therapeutic action of terpenoids of essential oil in uncommon plants like Elsholtzia stauntonii, Agastache foenic-ulum, Monarda fistulosa, Perovskia atri-plicifolia, Majorana hortensis, therefore the study for these plants application in phyto-therapy is timely. The study for componen-tial content of essential oil of 18 uncommon species from Lamiaceae family from the collection of Nikitsky Botanical Garden to increase therapeutic possibilities and their practical use in phytotherapy was the purpose of this paper. The plant species under study were introduced to the South Coast of Crimea from different ecological and geographic zones in seeds from botanical gardens of Europe. Methods. Every species was represented by 3-20 samples, which were studied by biomorpholofical and principal economically valuable features. The article presents the generalization and analysis of long-time studies for biologically active substances from 18 species of aromatic plants from Lamiaceae family. The content of essential oil was determined in a phase of mass blossom, from freshly harvested raw materials by means of hydro distillation at Ginsberg apparatuses. Componential content of essential oil was studied by the method of gas liquid chromatography. Results. Identification of the essential oils components allowed isolation of plant chemotypes with high content of valuable substances (methyl chavicol, carvacrol, pinen, thymol, and others). Highproductive samples (forms), prospective for industrial cultivation were isolated by the features complex. Based on the classification of A.D. Turova in phytotherapeutic action of plants and results of our studies, the isolated plant forms were distributed in 10 groups of usage in phytotherapy. On the example of Agastache foeniculum we showed that one and the same plant species may have different chemotypes, which have treatment and toxic action. Conclusion. The data obtained broaden and add the information about a chemical composition of plants and allow broadening the raw material base of medicinal plant by means of introduction of uncommon species from Lamiaceae family into cultivation.